Implikasi Politik dari Perubahan Kebijakan Kewarganegaraan terhadap Hubungan Diplomatik Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Kyla Jessica Veda; Azizah Harda Annafi’ah; Imam Aris Utomo (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
This study explores the political impacts of citizenship policy changes on Indonesia’s diplomatic relationships, particularly in the context of globalization and the movement of its diaspora. Indonesia currently maintains a single citizenship policy, preventing its citizens from holding dual nationality. This restriction often complicates the legal and emotional connections of Indonesians living abroad with their home country, while also limiting their economic contributions through remittances and investments. Conversely, many nations have adopted dual citizenship policies to maintain stronger connections with their diaspora and enhance their diplomatic influence. Using a qualitative approach with case studies focusing on countries with large Indonesian diasporas, such as Malaysia, Saudi Arabia, and the United States, this research highlights the potential benefits of dual citizenship. The findings indicate that allowing dual citizenship could strengthen Indonesia’s diplomatic ties and increase economic contributions from overseas Indonesians. However, there are challenges to implementation, including concerns over divided loyalty and complexities in legal enforcement. This paper suggests that Indonesia consider a carefully controlled introduction of dual citizenship, taking into account legal protections, economic benefits, and the role of the diaspora in promoting Indonesia’s interests abroad.